False-positive asynchronous-abdominal curtain sign mimicking pneumothorax in cats with severe pulmonary hyperinflation—case report - Donati, Pablo A.; Plotnikow, Gustavo A.; Boysen, Søren R. (Frontiers in Veterinary Science, 2026)
IntroductionThe asynchronous-abdominal curtain sign (A-ACS) is a suggestive ultrasound artifact for pneumothorax in veterinary medicine. However, its specificity has not been fully established.Case presentationWe describe two dyspneic cats displaying a prominent A-ACS despite the absence of findings strongly supportive of pneumothorax. Both cases had severe pulmonary hyperinflation secondary to expiratory flow limitation (feline lower airway disease and suspected anaphylaxis). Sonographic assessment revealed A-ACS and reduced diaphragmatic excursion. Medical management targeting bronchoconstriction and inflammation resulted in complete resolution of respiratory signs, normalization of the abdominal curtain sign (ACS), and improved diaphragmatic excursion in the monitored case.DiscussionThese findings suggest that severe pulmonary hyperinflation may represent a cause of false-positive A-ACS, likely resulting from diaphragmatic flattening and altered cardiophrenic mechanics.ConclusionClinicians should consider pulmonary hyperinflation in cats presenting with A-ACS to avoid misdiagnosis of pneumothorax and unnecessary interventions. Moreover, this sign may offer valuable insights into respiratory dynamics in feline obstructive airway disease.